Synthesis and characterization of L-tyrosine-conjugated quaternary ammonium salt chitosan and their cytocompatibility as a potential tissue engineering scaffold. Issue 7 (2nd May 2020) - Hu, Yasong; Zhan, Congcong; Zhou, Anduo; Zhang, Shanfeng; Chen, Juying; Huang, Xia
Abstract: A novel amino acid-modified biomacromolecule was designed and synthesized as the quaternary ammonium salt chitosan grafted-tyrosine (CA-g-Tyr) suitable for biomedical applications. L-tyrosine was grafted onto the quaternary ammonium salt chitosan (CA) by N-(3-dimethylaminopropy)-N-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS). The chemical structure of CA-g-Tyr was confirmed by Fourier transform infrared (FTIR) spectroscopy and 13 C-NMR. The change in the crystalline structure after the graft was characterized by differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD). The surface wettability and moisturizing performance of the CA-g-Tyr were also characterized. The CA-g-Tyr film possessed good hydrophilicity, and the mechanical tensile experiments showed that the introduction of tyrosine gave CA mechanical properties more suitable for blood vessel. Cell experiments showed that the endothelial cells can adhere and proliferate better on the surface of a CA-g-Tyr film than CA. The results confirm the favorable properties and biocompatibility of CA–g-Tyr with potential applications as scaffolds for tissue engineering.